Impact of a Core Ferrule Design on Fracture Resistance of Teeth Restored with Cast Post and Core. (22nd June 2016) - Shamseddine, Loubna; Chaaban, Farid
Abstract : Objectives . To investigate the influence of a contra bevel on the fracture resistance of teeth restored with cast post and core. Materials and Methods . Sixty plastic analogues of an upper incisor were endodontically treated and prepared with 6° internal taper and 2 mm of ferrule in order to receive a cast post and core. The prepared samples were divided into two groups (n = 30 ); the first group serves as control while the second group was prepared with an external 30° bevel on the buccal and lingual walls. All samples crowned were exposed to a compressive load at 130° to their long axis until fractures occurred. Fracture resistance loads were recorded and failure modes were also observed. Mann-Whitney test was carried out to compare the two groups. Results . Mean failure loads for the groups were, respectively, 1038.69 N (SD ±243.52 N) and 1078.89 N (SD ±352.21 N). Statistically, there was no significant difference between the two groups (P = 0.7675 > 0.05 ). Conclusion . In the presence of a ferrule and a crown in the anterior teeth, adding a secondary ferrule to the cast post and core will not increase the resistance to fracture.